Correlation of the gut microbiome and immune-related adverse events in gastrointestinal cancer patients treated with immune checkpoint inhibitors - Zhang, Yifan; Cheng, Siyuan; Zou, Hua; Han, Zihan; Xie, Tong; Zhang, Bohan; Dai, Die; Yin, Xiaochen; Liang, Yong; Kou, Yan; Tan, Yan; Shen, Lin; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
The wide application of immune checkpoint inhibitors has significantly improved the survival expectation of cancer patients. While immunotherapy brings benefits to patients, it also results in a series of immune-related adverse events (irAEs). Increasing evidence suggests that the gut microbiome is critical for immunotherapy response and the development of irAEs. In this prospective study, we recruited 95 patients with advanced/unresectable gastrointestinal cancers treated with immunotherapy and report a comprehensive analysis of the association of the gut microbiome with irAEs. Metagenome sequencing was used to analyze the differences in bacterial composition and metabolic pathways of baseline fecal samples. In summary, we identified bacterial species and functional pathways that might be associated with the occurrence of irAEs in gastric, esophageal, and colon cancers. Ruminococcus callidus and Bacteroides xylanisolvens were enriched in patients without severe irAEs. Several functional pathways involved in the urea cycle, including citrulline and arginine biosynthesis, were associated with irAEs. We also found that irAEs in different cancer types and toxicity in specific organs were associated with different gut microbiota profiles. These findings provide the basis for future mechanistic exploration.